A Codesign Approach for Conversational User Interfaces to Support College Students with Depression - de Souza, Paula Maia; Alves, Vanessa de Cássia; Pires, Isabella da Costa; Bleicher, Taís; Garcia, Franco Eusébio; da Silva, Grasiane Cristina; Neris, Vânia Paula de Almeida (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: The university context has demands that can increase the risk of depression and other mental disorders in students. Conversational User Interfaces (CUI) have been explored to support the prevention, diagnosis and therapy of people with depression. However, the design of these CUI, focused on college students, has not been deeply investigated. Objective: Based on this context, the objective of this paper is to propose a codesign approach for CUI to support college students with depression. Methodology: The Design Science Research method was used to propose, instantiate, and evaluate the design generated using the proposed approach. Results: The results suggest that the approach led to enjoyable CUI in this domain. Finally, some lessons learned are discussed.